A note on the exact formulas for certain $2$-color partitions - Guadalupe, Russelle (Comptes Rendus. Mathématique)
Let $p\le 23$ be a prime and $a_p(n)$ count the number of partitions of $n$ where parts that are multiple of $p$ come up with $2$ colors. Using a result of Sussman, we derive the exact formula for $a_p(n)$ and obtain an asymptotic formula for $\log a_p(n)$. Our results partially extend the work of Mauth, who proved the asymptotic formula for $\log a_2(n)$ conjectured by Banerjee et al.